2023
DOI: 10.1002/pon.6241
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions on the posttraumatic growth of adults with cancer: A systematic review and meta‐analysis of clinical trials

Nikolaos Vrontaras,
Georgios Koulierakis,
Iliana Ntourou
et al.

Abstract: BackgroundIt has been increasingly recognized that some people experience post‐traumatic growth (PTG) as a result of struggling with cancer.ObjectiveThis systematic review aims to identify psychosocial interventions that might facilitate PTG in adults with cancer.MethodsA search was conducted in PsycINFO, PubMed, Scopus, the Cochrane Library, and ProQuest up to 16 September 2022. The PRISMA guidelines were followed; all included interventional studies had to comprise 30 or more adults with cancer, using the Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Encouragingly, in a recent meta-analysis, Vrontaras and co-workers reported a range of interventions across 37 studies including cognitive behavioural therapy, mindfulness, expressive, educational and psychology-based approaches promoting posttraumatic growth with people with mixed and single types of cancer. 73 They report that overall, these interventions show moderate impact ( d = 0.65), regardless of sample, with cognitive behavioural therapy demonstrating a greater impact ( d = 1.24) that translates to an increase of 12 points to the total of the PTGI score, compared to 2 points in control groups. Although these findings suggest that posttraumatic growth can be facilitated with relaxation, education and self-disclosure in people being treated for or surviving cancer, it is not known whether they can be translated into palliative care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouragingly, in a recent meta-analysis, Vrontaras and co-workers reported a range of interventions across 37 studies including cognitive behavioural therapy, mindfulness, expressive, educational and psychology-based approaches promoting posttraumatic growth with people with mixed and single types of cancer. 73 They report that overall, these interventions show moderate impact ( d = 0.65), regardless of sample, with cognitive behavioural therapy demonstrating a greater impact ( d = 1.24) that translates to an increase of 12 points to the total of the PTGI score, compared to 2 points in control groups. Although these findings suggest that posttraumatic growth can be facilitated with relaxation, education and self-disclosure in people being treated for or surviving cancer, it is not known whether they can be translated into palliative care settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, these interventions only indirectly targeted posttraumatic growth and it has been suggested that some cognitive and educational approaches may result in too much distress and be paralysing. 75 Given the demonstrated links between posttraumatic growth and better psychological wellbeing, quality of life and the positive outcomes in those with cancer, 73 there appears to be a need for more work exploring interventions that specifically seek to foster posttraumatic growth in the palliative care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, enhancing the resilience of ENs during the restructuring phase can facilitate the achievement of PTG. 31 Resilience, defined as the ability to bounce back when individuals face adversity, trauma, misfortune or change, encompasses positive feedback, self-motivation and a focus on the future. Resilient individuals tend to maintain emotional composure and are more likely to successfully complete cognitive restructuring.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review of meta-analyses and the RE-AIM framework demonstrate that app- and website-based interventions have a wide range of effects and are highly used by different (international and multilingual) patients with cancer. However, the use and accessibility of app- and website-based MBIs for patients with cancer have been constrained because of service fees and patient mobility limitations [ 48 ]; app- and website-based MBIs are mainly conducted in high-income countries. The possible explanation is the distinction between communication and economy; some high-income countries may have national health services in place to promote app- and website-based MBIs, whereas developing nations may not.…”
Section: Discussionmentioning
confidence: 99%